Lemierre’s syndrome variant of the gut - Mellor, Thomas E. (BMJ Case Rep, 2017)
Infectious suppurative thrombophlebitis of the portal venous system, referred to as pylephlebitis, is a rare complication of intra-abdominal inflammatory processes. Advances in diagnostics and antibiotics have improved survival, but mortality remains remarkably high even in the most recent literature. The majority of patients have concomitant bacteraemia on presentation most commonly with typical gastrointestinal (GI) organisms. On rare occasion, patients have culture positive Fusobacterium, which has recently been associated with occult GI and genitourinary malignancies. Here, we describe a patient presenting with pylephlebitis and Fusobacterium bacteraemia who responded well to medical therapy, review pertinent literature and discuss the benefits of screening endoscopy in this patient population.